2015
DOI: 10.1080/01621459.2014.931859
|View full text |Cite
|
Sign up to set email alerts
|

Index Models for Sparsely Sampled Functional Data

Abstract: The regression problem involving functional predictors has many important applications and a number of functional regression methods have been developed. However, a common complication in functional data analysis is one of sparsely observed curves, that is predictors that are observed, with error, on a small subset of the possible time points. Such sparsely observed data induces an errors-in-variables model, where one must account for measurement error in the functional predictors. Faced with sparsely observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In some fields of functional data analysis, noisy random functions have already been studied intensively; a body of literature on this topic encompassing functional linear regression, functional principal components, continuous additive models, etc. can be found in Yao et al (2005), Crambes et al (2009), Paul and Peng (2009), Jiang and Wang (2010), Li and Hsing (2010), Wu et al (2010), Müller et al (2013), Radchenko et al (2015), Hsing and Eubank (2015) and Zhang and Wang (2016), among others. In those works, noisy functional data are typically either (i) pre-smoothed in the first step, and then statistical analysis is performed for the smoothed approximants of the data curves; or (ii) the statistical procedure in question is revisited, and suitably applied directly to the available discrete noisy observations.…”
Section: Introductionmentioning
confidence: 94%
“…In some fields of functional data analysis, noisy random functions have already been studied intensively; a body of literature on this topic encompassing functional linear regression, functional principal components, continuous additive models, etc. can be found in Yao et al (2005), Crambes et al (2009), Paul and Peng (2009), Jiang and Wang (2010), Li and Hsing (2010), Wu et al (2010), Müller et al (2013), Radchenko et al (2015), Hsing and Eubank (2015) and Zhang and Wang (2016), among others. In those works, noisy functional data are typically either (i) pre-smoothed in the first step, and then statistical analysis is performed for the smoothed approximants of the data curves; or (ii) the statistical procedure in question is revisited, and suitably applied directly to the available discrete noisy observations.…”
Section: Introductionmentioning
confidence: 94%
“…Then we obtain the estimate r S k puq " p b pkq 0 . We also develop a basis expansion approach (Radchenko et al, 2015) to estimate C k and S k , where details can be found in Section C of the Supplementary Material.…”
Section: Partially Observed Functional Predictormentioning
confidence: 99%
“…Other nonparametric functional regression approaches are Preda (2007); Lian (2007,2011). Semiparametric approaches are relatively less-studied and scattered in the literature including Ait-Saidi et al (2008); Müller and Yao (2008); Chen et al (2011); McLean et al (2014); Zhu et al (2014); Radchenko et al (2015), among some others.…”
Section: Introductionmentioning
confidence: 99%